2017
DOI: 10.1093/annonc/mdx125
|View full text |Cite
|
Sign up to set email alerts
|

Plasma ctDNA RAS mutation analysis for the diagnosis and treatment monitoring of metastatic colorectal cancer patients

Abstract: Background RAS assessment is mandatory for therapy decision in metastatic colorectal cancer (mCRC) patients. This determination is based on tumor tissue, however, genotyping of circulating tumor (ct)DNA offers clear advantages as a minimally invasive method that represents tumor heterogeneity. Our study aims to evaluate the use of ctDNA as an alternative for determining baseline RAS status and subsequent monitoring of RAS mutations during therapy as a component of routine clinical practice.Patients and methods… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

17
313
2
4

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 299 publications
(336 citation statements)
references
References 16 publications
17
313
2
4
Order By: Relevance
“…First, prior treatment type at time of blood draw or tissue biopsy was not considered. It was previously reported that KRAS status in ctDNA could be affected by specific therapeutic pressure such as administration of EGFR antibodies . Indeed, 7 out of 20 patients who had KRAS alterations only in ctDNA received anti‐EGFR therapies prior to their ctDNA analyses in this series.…”
Section: Discussionmentioning
confidence: 76%
“…First, prior treatment type at time of blood draw or tissue biopsy was not considered. It was previously reported that KRAS status in ctDNA could be affected by specific therapeutic pressure such as administration of EGFR antibodies . Indeed, 7 out of 20 patients who had KRAS alterations only in ctDNA received anti‐EGFR therapies prior to their ctDNA analyses in this series.…”
Section: Discussionmentioning
confidence: 76%
“…The first blinded prospective study that evaluated KRAS mutation status in ctDNA using Intplex, a quantitative PCR‐based method using originally designed specific primers for multiple gene mutations , in mCRC showed high concordance (94%) and specificity (98%) compared with tissue analyses . The OncoBEAM RAS CRC assay is now available as the only test for detecting RAS mutations in ctDNA with European Conformity in vitro diagnostic (CE‐IVD) study; it can accurately detect up to 34 mutations in exons 2, 3, and 4 of KRAS and NRAS genes, using the BEAMing technology . One of the largest cohort prospective studies revealed that the accuracy raised up to 95.6% in patients with liver metastases .…”
Section: Identification Of Biomarkers Related To Resistance To Epidermentioning
confidence: 99%
“…We previously reported the detection of KRAS mutations in cfDNA from 5 of 55 mCRC patients (9%) with wild-type KRAS in their primary tumors [23]. Other researchers reported that KRAS mutation in cfDNA is a negative biomarker of EGFR blockade chemotherapy [23][24][25][26][27].…”
Section: Predictive Information For Metastatic Diseasementioning
confidence: 98%
“…Some researchers have detected emerging KRAS mutation in cfDNA from patients with secondary resistance to EGFR blockade chemotherapy [24][25][26][28][29][30]. Emerging BRAF mutation [25] and emerging EGFR mutation [26,30] are induced by EGFR blockade.…”
Section: Predictive Information For Metastatic Diseasementioning
confidence: 99%